Cancers in Australia in 2010 attributable to inadequate consumption of fruit, non‐starchy vegetables and dietary fibre. (October 2015) - Nagle, Christina M.; Wilson, Louise F.; Hughes, Maria Celia B.; Ibiebele, Torukiri I.; Miura, Kyoko; Bain, Christopher J.; Whiteman, David C.; Webb, Penelope M.
Abstract Objectives: To estimate the number and proportion of cancers occurring in Australia in 2010 attributable to consumption deficits in fruit, non‐starchy vegetables and dietary fibre. Methods: We estimated the population attributable fraction (PAF) for cancers causally associated with inadequate intake of fruit and non‐starchy vegetables (oral cavity, pharynx, oesophageal squamous cell carcinoma, stomach, larynx); inadequate intake of fruit (lung); and insufficient intake of fibre (colorectum). We used standard formulae incorporating prevalence of exposure (1995 National Nutrition Survey) and relative risks from independent studies. Results: Overall, 1, 555 (1.4% of all) and 311 (0.3% of all) cancers were attributable to inadequate intakes of fruit and non‐starchy vegetables, respectively. A further 2, 609 colorectal cancers (18% of colorectal) were attributable to insufficient fibre intake. If Australians increased their fibre intake by eating the recommended daily intakes of fruit and vegetables, an estimated 1, 293 (8.8%) colorectal cancers could be prevented. Conclusions: One in six colorectal cancer cases was attributable to inadequate intake of dietary fibre and about 1, 800 cancers at other sites were attributable to insufficient fruit and non‐starchy vegetable consumption. Implications: Increasing the proportion of Australians who consume the recommended intake of fruit, vegetables and fibre could prevent up to 4% of all cancers.